Immediate Effects of Footwear Design on In‐Shoe Plantar Pressures, Impact Forces and Comfort in Women With Plantar Heel Pain - Melinda M. Franettovich Smith; Wolbert van denHoorn; Adele van denHoek; Graham Kerr; Sheree E. Hurn (Journal of Foot and Ankle Research, 2025)
ABSTRACT Background Footwear is often recommended in the management of plantar heel pain (PHP), theoretically to reduce tissue stress during standing and walking; however, limited data exist to guide footwear design and recommendations. Methods Plantar pressures, impact forces and comfort during walking were recorded in 29 women with PHP (mean age 47 ± 12 years) in six randomised shoe and insert conditions. A test shoe (polyurethane outsole, 14‐mm heel‐toe pitch) was compared to a control shoe (rubber outsole, 4‐mm heel‐toe pitch), and within the test shoe, five different insoles that varied by material, density and arch contouring were also compared. Results The test shoe reduced heel peak pressure (15%, p < 0.01) and reduced the loading rate but not the peak magnitude of the vertical ground reaction force (average loading rate reduction: 7%, p < 0.01; maximum loading rate: 29%, p < 0.01) and was more comfortable (47%–67%, p < 0.01) compared to the control shoe. Within the test shoe, dual‐density inserts with arch contouring showed lower heel peak pressure compared to a lightweight flat insert (11%–12%, p < 0.03). The insert with the firmest material and higher arch contouring showed higher midfoot peak pressure (16%–21%, p < 0.01) compared to other inserts. Forefoot peak pressure did not differ between shoe or insert conditions (p > 0.05). There were no differences in impact forces or comfort between the different inserts within the test shoe (p > 0.05). Conclusion Findings suggest that shoe and insert properties are both important and provide data to guide footwear design and management recommendations for PHP.